Portfolio capital investment in Malaysia / Irfah Najihah Basir Malan - Basir Malan, Irfah Najihah (Institute of Business Excellent (IBE), 2010)
The main objective of this paper is to highlight a conceptual understanding on the portfolio capital investment in Malaysia. It constitutes an overview of features, facts and figures over the financial account in the Malaysia balance of payment, Malaysia external trade, heightened exposure to mobile capital flows, total of portfolio capital inflow by country, total portfolio investment by country, the net inflow of portfolio capital investment in total and from four major countries and currency exchange rate of major portfolio capital investment by country. The findings of the paper show that the trends of portfolio capital investment are on uptrend after Asian crisis. Asian crisis had brought terrible effects to Malaysia especially during Asian crisis. The implication of this paper is to provide a platform for industry players and regulators to implement policies that maximize the benefits from foreign portfolio capital investment flows and minimize their potential risks. The paper aims to attract the global attention towards the issues of portfolio capital investment in Malaysia. The present trends of portfolio capital investment in Malaysia captured in this paper can tell all about its future challenges in the global investment perspective